Psychosocial impact of undergoing prostate cancer screening for men with BRCA1 or BRCA2 mutations. (22nd June 2018) - Bancroft, Elizabeth K.; Saya, Sibel; Page, Elizabeth C.; Myhill, Kathryn; Thomas, Sarah; Pope, Jennifer; Chamberlain, Anthony; Hart, Rachel; Glover, Wayne; Cook, Jackie; Rosario, Derek J.; Helfand, Brian T.; et al.
Abstract : Objectives: To report the baseline results of a longitudinal psychosocial study that forms part of the IMPACT study, a multi‐national investigation of targeted prostate cancer (PCa) screening among men with a known pathogenic germline mutation in the BRCA1 or BRCA2 genes. Particpants and Methods: Men enrolled in the IMPACT study were invited to complete a questionnaire at collaborating sites prior to each annual screening visit. The questionnaire included sociodemographic characteristics and the following measures: the Hospital Anxiety and Depression Scale (HADS), Impact of Event Scale (IES), 36‐item short‐form health survey (SF‐36), Memorial Anxiety Scale for Prostate Cancer, Cancer Worry Scale‐Revised, risk perception and knowledge. The results of the baseline questionnaire are presented. Results: A total of 432 men completed questionnaires: 98 and 160 had mutations in BRCA1 and BRCA2 genes, respectively, and 174 were controls (familial mutation negative). Participants' perception of PCa risk was influenced by genetic status. Knowledge levels were high and unrelated to genetic status. Mean scores for the HADS and SF‐36 were within reported general population norms and mean IES scores were within normal range. IES mean intrusion and avoidance scores were significantly higher in BRCA1 / BRCA2 carriers than in controls and were higher in men with increased PCa risk perception. At the multivariate level, risk perception contributed more significantly to variance in IES scores than genetic status. Conclusion: This is the first study to report the psychosocial profile of men with BRCA1 / BRCA2 mutations undergoing PCa screening. No clinically concerning levels of general or cancer‐specific distress or poor quality of life were detected in the cohort as a whole. A small subset of participants reported higher levels of distress, suggesting the need for healthcare professionals offering PCa screening to identify these risk factors and offer additional information and support to men seeking PCa screening.